2017
DOI: 10.1158/1940-6207.capr-16-0278
|View full text |Cite
|
Sign up to set email alerts
|

Unmetabolized Folic Acid, Tetrahydrofolate, and Colorectal Adenoma Risk

Abstract: In a randomized trial of folic acid supplementation for the prevention of colorectal adenomas, we previously found indications of increased risk during later treatment and follow-up. This could have been due to the unmetabolized folic acid or natural reduced and methylated folates to which it is metabolized. In post hoc analyses, we measured methylated folates (mF, the sum of 5-methyl-tetrahydrofolate and 4-alfa-hydroxy-5-methyl-THF) and unmetabolized folic acid (UFA) concentrations in the serum of 924 partici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
0
13
0
2
Order By: Relevance
“…These observations strengthen our working hypothesis that MeFox in serum may not be entirely generated post-blood collection from 5-methylTHF oxidation. We therefore question the approach of using a sum indicator called "methylated folate" (sum of 5-methylTHF and MeFox) to interpret folate status (24). Instead, we suggest to separately report results for 5-methylTHF and MeFox to provide broader utility to investigators.…”
Section: Discussionmentioning
confidence: 99%
“…These observations strengthen our working hypothesis that MeFox in serum may not be entirely generated post-blood collection from 5-methylTHF oxidation. We therefore question the approach of using a sum indicator called "methylated folate" (sum of 5-methylTHF and MeFox) to interpret folate status (24). Instead, we suggest to separately report results for 5-methylTHF and MeFox to provide broader utility to investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary folate deficiency causes several developmental disorders, most notably neural tube defects, many of which are prevented by adequate folate supplementation [ 1 , 2 ]. Likewise, epidemiological studies suggest that sufficient dietary folate diminishes cancer initiation, though this effect appears to be cancer type specific [ 3 , 4 , 5 ]. Genetic polymorphisms in several folate enzymes, most notably methylenetetrahydrofolate reductase (MTHFR), have also been associated with increased risk of several cancers [ 6 , 7 , 8 ], underscoring the role of folate metabolism in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some recent human studies, including randomized clinical trials, suggest risks for colon, breast or prostate cancers may be increased in those taking high doses of folic acid from supplements (Charles, Ness, Campbell, Davey Smith, & Hall, ; Cole et al, ; Figueiredo et al, ; Hirsch et al, ; Stolzenberg‐Solomon et al, ) in the context of a folic acid fortified diet. Notably, a randomized clinical trial of colorectal adenoma suggested the risk of recurrent advanced colorectal adenoma or multiple adenomas increased with excessive levels of folate (Rees et al, ). Several other trials reported no such effect (Logan, Grainge, Shepherd, Armitage, & Muir, ; Song et al, ; Wu et al, ), although they had shorter follow‐up periods.…”
Section: Introductionmentioning
confidence: 99%